Olympia, Griechenland. Die Arbeiten der Jahre 2016 und 2017 - Senff, Reinhard (e-Forschungsberichte des DAI, 2018)
The excavations in Olympia in 2016 and 2017 focused on the area south of the South Stoa, where according to ancient sources a kind of agora, an open place for gatherings and commercial activities can be assumed. The trenches which were opened directly south of the middle part of the stoa, however, so far brought to light mainly remains of the Late Roman and Early Christian Periods, a tile kiln, and two graves but no traces of earlier activities which could be connected with public activities at an agora.